2015
DOI: 10.1097/jsm.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Current AHA Guidelines and Proposal of New Guidelines for the Preparticipation Examination of Athletes

Abstract: In a patient population without any adverse cardiovascular events, the currently recommended AHA 12-elements have an unacceptably high rate of false positives. Newer screening guidelines are needed, with fewer false positives and evidence-based updates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 12 publications
0
25
1
1
Order By: Relevance
“…The generally broad and non-specific questions also elicit a high number of positive responses in athletes. In college athletes, at least one positive cardiovascular symptom, or family history response, was reported by 24–43% of athletes during preparticipation evaluations using either the AHA 12-point or PPE-4 questionnaires 33 34. In high school athletes, initial positive history responses were reported by 68% of athletes undergoing a heart screen using the PPE-4 history questions 35.…”
Section: Evidence Evaluating the Efficacy Of Preparticipation Screenimentioning
confidence: 99%
See 2 more Smart Citations
“…The generally broad and non-specific questions also elicit a high number of positive responses in athletes. In college athletes, at least one positive cardiovascular symptom, or family history response, was reported by 24–43% of athletes during preparticipation evaluations using either the AHA 12-point or PPE-4 questionnaires 33 34. In high school athletes, initial positive history responses were reported by 68% of athletes undergoing a heart screen using the PPE-4 history questions 35.…”
Section: Evidence Evaluating the Efficacy Of Preparticipation Screenimentioning
confidence: 99%
“…Nevertheless, some authorities do recommend the use of a resting 12-lead ECG during the preparticipation cardiovascular screening of athletes 33 34 36. Several studies have examined the ability of history, physical examination, and ECG to detect potentially life-threatening cardiovascular disease (which does not necessarily equate with identifying individuals who will actually experience a cardiac event).…”
Section: Evidence Evaluating the Efficacy Of Preparticipation Screenimentioning
confidence: 99%
See 1 more Smart Citation
“…False‐positive rates in the meta‐analysis were 6% for ECG, 8% for history, and 10% for physical examination [23]. Recent studies of current cardiac history questionnaires, however, have demonstrated a very high positive response rate in student athletes, ranging from 14% to 68% [25‐27]. In addition, sorting through the numerous and often‐vague responses on cardiac symptom questionnaires is challenging, with no standard response or secondary investigations instituted by the primary care or sports medicine communities.…”
Section: Introductionmentioning
confidence: 99%
“…Although the natural history of previously undetected conditions is not known, it has been shown that active management of hypertrophic cardiomyopathy (HCM) and arrythmogenic right ventricular cardiomyopathy (ARVC) improves outcomes. A prospective study compared 33,735 athletes screened with ECG with unscreened nonathletes [27]. In the screened athletes, there were 22 cases of HCM detected, none of whom died during the 8‐year follow‐up period, and 1 screened athlete who was undetected and died.…”
Section: Introductionmentioning
confidence: 99%